Nilai-Nilai Al-Quran Surat Thaha Ayat 132 terhadap Tanggung Jawab Orang Tua dalam Pendidikan Agama Anak - Rofiah; Dedih Surana (UNISBA Press, 2022)
Abstract. Allah SWT revealed Surah Thaha verse 132. Allah commanded Rasulullah SAW in this verse so that he invites all family members to perform prayers. Based on this, there is a problem formulation, namely (1) What are the opinions of the commentators about the main content of the Al-Quran Surah Thaha verse 132? (2) What is the essence in the Quran? (3) How do experts view parental responsibility? on children's religious education in the Al-Quran Surah Tahaha verse 132? (4) What are the educational values and implications of Al-Quran Surah Thaha verse 132 on the responsibilities of parents in children's religious education? This study uses a descriptive-analytical method of collection technique, namely library research by examining in depth various interpretations. T has been regulated in law no. 1 of 1974 concerning the main points of marriage, article 45 paragraph 1, namely: